Mild TBI and risk of Parkinson disease: A Chronic Effects of Neurotrauma Consortium Study - Gardner, Raquel C; Byers, Amy L; Barnes, Deborah E; Li, Yixia; Boscardin, John; Yaffe, Kristine (Neurology, 2018)
Our aim was to assess risk of Parkinson disease (PD) following traumatic brain injury (TBI), including specifically mild TBI (mTBI), among care recipients in the Veterans Health Administration. In this retrospective cohort study, we identified all patients with a TBI diagnosis in Veterans Health Administration databases from October 2002 to September 2014 and age-matched 1:1 to a random sample of patients without TBI. All patients were aged 18 years and older without PD or dementia at baseline. TBI exposure and severity were determined via detailed clinical assessments or ICD-9 codes using Department of Defense and Defense and Veterans Brain Injury Center criteria. Baseline comorbidities and incident PD more than 1 year post-TBI were identified using ICD-9 codes. Risk of PD after TBI was assessed using Cox proportional hazard models adjusted for demographics and medical/psychiatric comorbidities. Among 325,870 patients (half with TBI; average age 47.9 ± 17.4 years; average follow-up 4.6 years), 1,462 were diagnosed with PD during follow-up. Compared to no TBI, those with TBI had higher incidence of PD (no TBI 0.31%, all-severity TBI 0.58%, mTBI 0.47%, moderate-severe TBI 0.75%). In adjusted models, all-severity TBI, mTBI, and moderate-severe TBI were associated with increased risk of PD (hazard ratio [95% confidence interval]: all-severity TBI 1.71 [1.53-1.92]; mTBI 1.56 [1.35-1.80]; moderate-severe TBI 1.83 [1.61-2.07]). Among military veterans, mTBI is associated with 56% increased risk of PD, even after adjusting for demographics and medical/psychiatric comorbidities. This study highlights the importance of TBI prevention, long-term follow-up of TBI-exposed veterans, and the need to determine mechanisms and modifiable risk factors for post-TBI PD.